The control of upper body segment speed and velocity during the golf swing - Horan, S. A.; Kavanagh, J. J. (Sports Biomechanics, 2012)
Understanding the dynamics of upper body motion during the downswing is an important step in determining the control strategies required for a successful and repeatable golf swing. The purpose of this study was to examine the relationship between head, thorax, and pelvis motion, during the downswing of professional golfers. Three-dimensional data were collected for 14 male professional golfers (age 27 ± 8 years, golf-playing experience 13.3 ± 8 years) using an optical motion analysis system. The amplitude and timing of peak speed and peak velocities were calculated for the head, thorax, and pelvis during the downswing. Cross-correlation analysis was used to examine the strength of coupling and phasing between and within segments. The results indicated the thorax segment had the highest peak speeds and peak velocities for the upper body during the downswing. A strong coupling relationship was evident between the thorax and pelvis (average R 2 = 0.92 across all directions), while the head and thorax showed a much more variable relationship (average R 2 = 0.76 across all directions). The strong coupling between the thorax and pelvis is possibly a method for simplifying the motor control strategy used during the downswing, and a way of ensuring consistent motor patterns.